2022
DOI: 10.1038/s41598-022-27141-7
|View full text |Cite
|
Sign up to set email alerts
|

Global urban homogenization and the loss of emotions

Abstract: Urban expansion is generating unprecedented homogenization of landscapes across the world. This uniformization of urban forms brings along dramatic environmental, social, and health problems. Reverting such processes requires activating people’s sense of place, their feeling of caring for their surroundings, and their community engagement. While emotions are known to have a modulating effect on behavior, their role in urban transformation is unknown. Drawing on large cognitive-psychological experiments in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Our work highlights the impact of a settlement’s position within a settlement network on its morphological homogeneity. This homogeneity harbours a number of potentially negative impacts on various aspects of urban life 2 , 3 , 5 – 7 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work highlights the impact of a settlement’s position within a settlement network on its morphological homogeneity. This homogeneity harbours a number of potentially negative impacts on various aspects of urban life 2 , 3 , 5 – 7 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…the lack of urban morphometric variability, often goes hand in hand with settlement sprawl and can have negative impacts on urban vibrancy 2,3 , local character [4][5][6][7] , and the environment [8][9][10][11][12][13] . It has also been shown that the homogenization of the landscape in peri-urban areas can lead to negative emotional responses 14 , which is a phenomenon that has been observed worldwide 1 . An important factor driving morphological homogenization is the increased accessibility of settlements with motorized individual transport 15,16 .…”
Section: Settlement Relationships and Their Morphological Homogeneity...mentioning
confidence: 99%
“…The continuous advancement of urbanization has led to a constant expansion of urban population and size. The pursuit of interests without restraint and blind expansion has resulted in severe homogenization among cities, lacking regional characteristics [1][2][3]. At the same time, the process of industrialization has led to a significant encroachment of urban green spaces by buildings, and the reduction in green space areas has greatly impacted the living environment [4].…”
Section: Introductionmentioning
confidence: 99%